Risk of herpes simplex virus type 2 acquisition increases over early adulthood: evidence from a cohort study. Issue 2 (17th August 2006) - Dickson, N; van Roode, T; Herbison, P; Taylor, J; Cunningham, A; Paul, C
Abstract : Design/setting: A cohort study of 1037 people born in Dunedin, New Zealand, in 1972 or 1973. Participants: At assessment at age 32 years, 884 participants (432 women and 452 men; 87.1% of the surviving cohort) provided both sera and information on sexual behaviour. Main outcome measures: The proportion of participants with antibodies to HSV-2 infection at ages 26 and 32 years was measured, and the incidence rates from first coitus to age 26 years and from age 26 to 32 years calculated, adjusting for the number of sexual partners and same-sex contact in these age periods. Results: At age 32 years, 14.6% of men and 22.5% of women had antibodies to HSV-2. The incidence rates for men and women from first coitus to age 26 years were, respectively, 6.5 and 14.3 per 1000 person-years. The incidence rates for men and women from age 26–32 years, respectively, were 14.3 and 15.8 per 1000 person-years. When adjusted for sexual behaviour, the incidence rate ratio, comparing the older with the younger age periods, was 2.9 (95% confidence interval (CI) 1.7 to 4.9) for men and 2.0 (1.2 to 3.4) for women. The adjusted incidence rate ratio when comparing women to men from first coitus to age 26 years was 2.5 (1.6 to 4.0), and from age 26–32 years was 1.3 (0.78 to 2.2). A test for interaction indicated that men and women had different patterns of incidence over time (p = 0.039). Conclusion: In the general population, the risk of acquiring HSV-2 infection seems to increase with age at least to the early 30s, and differences in risk of acquisition for women compared with men become less with age. Health promotion and treatment to control HSV-2 infection should be aimed at all ages, not just at the young.